ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN SISWA DALAM MENENTUKAN UNSUR-UNSUR INTRINSIK CERPEN FABEL - Ahmad Ridwan Mansur; Lintang Kironoratri; Lovika Ardana Riswari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading ability has a big influence on Indonesian language learning. Reading ability has an influence on Indonesian language learning, one of which is determining the elements in short stories. This research aims to find out what factors influence students' ability to determine the intrinsic elements in short stories. This research uses qualitative research with a case study approach. Data collection techniques in this research include observation, interview and documentation stages. The informants in this research were 16 class IV students at SD N Doropayung 01 Pati and class IV teachers. Data analysis techniques include data reduction, data presentation and drawing conclusions. The subjects in this research were 6 fourth grade students at SDN Doropayung 01 who were selected by researchers in the categories of 3 students with a high level of learning ability, and 3 students with a low level of learning ability. The results of this research are that the learning ability of fourth grade students at SD N Doropayung 01 in Indonesian language subjects is influenced by intrinsic factors including: interest, motivation and cognitive ability. Meanwhile, extrinsic factors include: school environment, family environment, and community environment.